2020
DOI: 10.1037/cdp0000297
|View full text |Cite
|
Sign up to set email alerts
|

“A lot of us have a very difficult time reconciling what being Muslim is”: A phenomenological study on the meaning of being Muslim American.

Abstract: Objectives:Little is known about the lived experiences of Muslim Americans and what it means to identify as "Muslim American" within the sociopolitical context of Islamophobia. Although xenophobia, racism, and religious discrimination have been shown to impact identity development, it is unclear how Muslim American youth negotiate and make sense of their identities against this backdrop. Method: A qualitative, phenomenological approach guided the research design to explore how 11 Muslim American late adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…For example, those who identified as Muslim felt particular pressure as spokespeople for a religion that spans multiple countries and cultures. This mirrors the findings of Wang et al (2019), who found that Muslim Americans struggle to balance their desire for individuality within the group, while still presenting a united front. Black/African American participants felt responsible for educating their classmates about healthcare disparities that impact their communities.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…For example, those who identified as Muslim felt particular pressure as spokespeople for a religion that spans multiple countries and cultures. This mirrors the findings of Wang et al (2019), who found that Muslim Americans struggle to balance their desire for individuality within the group, while still presenting a united front. Black/African American participants felt responsible for educating their classmates about healthcare disparities that impact their communities.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding religious identity, Muslim students face the challenge of establishing their individuality within a religion that spans multiple continents and cultures, while simultaneously feeling compelled to appear as a homogeneous group (Wang, Raja, & Azhar, 2019).…”
Section: Diversity Of the Genetic Counseling Professionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is only one mosque in the region, and some participants spoke about the challenge of building relationships even within the Muslim community attributable to differences in language preferences. Other participants experienced themselves as minorities within this community (e.g., ethnically Kurdish) or spoke of the challenges of being perceived by non-Muslims as a singular group, similar to findings reported by Wang, Raja, and Azhar (2020).…”
Section: Resultssupporting
confidence: 64%
“…Bolstering this conceptualization is the fact the racialization process has extended to non-Muslims that people think are Muslim (e.g., Sikhs, South Asians of other religious, Christian Arabs) creating a "Muslim-like" identity group that has been racialized as Muslims (Meeussen et al, 2013;Abdulrahim, James, Yamout, & Baker, 2012). And, indeed, the context of Islamophobia has been connected to individuals conceptualizing their own identity as Muslim (Wang, Raja, & Azhar, 2019) and working towards combating racism and prejudice (Cesari, 2014;Garner & Selod, 2015;Selod, 2015;Meer, 2019).…”
Section: Racialization Islamophobia and Discriminationmentioning
confidence: 99%